A Prototype of a biomimetic scallop robot with bivalve propulsion and a hydrodynamic model for its velocity - Cheng-Hsien Lin; Cheng-Chuan Lin; Pei-Chun Lin; Fu-Ling Yang (Journal of Applied Science and Engineering)
This work presents the development, test, and analysis of a scallop robot prototype that generates jet propulsion with cyclic bivalve clapping motion. Through observing the real scallop swimming and understanding of its organ function, the robot was made of a streamlined fiberglass lower shell and a flat Plexiglas upper disk driven to clap periodically by a built-in RC motor and crank-slider four-bar linkage. Two jet holes were created at the rear side of the lower shell and a water guide towards the jet holes were created by silica gel to mimic the cavity between the mantle and adductor muscle of a real scallop. The robot performance was evaluated by its forward velocity U(t) and systematic experiments were conducted to study how the cycle-averaged velocity varies with the clapping frequency and amplitude. A complementing hydrodynamic model is also developed for the scallop motion. A general trend that U increased with the clapping frequency was observed from both the experimental data and the model prediction but more complex correlation with the clapping amplitude was revealed. As a result, the bivalve propulsion implemented in the current scallop robot is feasible but requires weight reduction and improvement on flow manipulation.